The Role of Extracellular Vesicles in Embryo Implantation - Chen, Kaiyu; Liang, Junyong; Qin, Ti; Zhang, Yunchao; Chen, Xi; Wang, Zhengguang (Frontiers in Endocrinology, 2022)
Extracellular vesicles (EVs) are membrane-coating nanoparticles derived from cells. The effect of cell-to-cell communication mediated by EVs has been investigated in different fields of physio-logical as well as pathological process in recent years. Reproduction, regarded as a definitive characteristic of organisms, has been a focus in both animal and medical sciences. It is well agreed that implantation is a critical event during early pregnancy in viviparous animals, and a proper implantation is essential for the establishment and maintenance of normal pregnancy. However, successful implantation requires the synchronized development of both the uterus and the embryo, therefore, in which well communication and opportune regulation are necessary. This review focuses on the progression of studies that reveal the role of EVs in early pregnancy, especially during implantation. According to studies on this field, EVs are produced and exist in the environment for implantation. It has been proved that different types of EVs derived from different tissues have positive influences on embryo implantation. With their cargos of proteins and nucleic acids (especially microRNAs), EVs exert their effects including information transportation, immune stimulation and regulation of gene expression.